2016
DOI: 10.1164/rccm.201602-0265oc
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure Improves Quality of Life in Women with Obstructive Sleep Apnea. A Randomized Controlled Trial

Abstract: In women with moderate or severe OSA, 3 months of CPAP therapy improved QoL, mood state, anxiety and depressive symptoms, and daytime sleepiness compared with conservative treatment. Clinical trial registered with www.clinicaltrials.gov (NCT02047071).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 45 publications
6
51
0
2
Order By: Relevance
“…As previously summarized, CPAP was effective in some studies (Campos‐Rodriguez et al., ; Diamanti et al., ) and not in some others (Barnes et al., ; Gagnadoux et al., ). CPAP treatment did not resolve depressive symptoms in many OSA patients and persistent depressive symptoms were strongly associated with EDS (Gagnadoux et al., ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As previously summarized, CPAP was effective in some studies (Campos‐Rodriguez et al., ; Diamanti et al., ) and not in some others (Barnes et al., ; Gagnadoux et al., ). CPAP treatment did not resolve depressive symptoms in many OSA patients and persistent depressive symptoms were strongly associated with EDS (Gagnadoux et al., ).…”
Section: Discussionmentioning
confidence: 93%
“…In a recent RCT, with 307 female patients with moderate to severe OSA, Campos‐Rodriguez et al. showed significant improvement in depression after 3 months of CPAP therapy compared to conservative treatment (Campos‐Rodriguez et al., ). In a meta‐analysis, including 19 trials, CPAP treatment was shown to be effective in improving depression and a greater benefit of treatment was observed especially in patients with higher depression scores at baseline (Povitz et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The main strengths of our work include the use of older mice that were 18 months of age and the use of a conventional mouse strain, which allowed us to assess the cardiovascular consequences associated with IH exposure without other confounding factors or co‐morbidities. In addition, we used female mice rather than male mice due to the absence of relevant studies in female mice and the late emergence of sexually dimorphic cardiovascular outcomes with increased susceptibility in women …”
Section: Discussionmentioning
confidence: 99%
“…27 A RCT involving only women showed improvement in QoL measures after 3 months of PAP therapy as determined by the Quebec Sleep Questionnaire. 28 A recent meta-analyses showed improvement in the medical and physical components of SF-36 with the use of CPAP therapy 29 in patients with OSA. A recent study showed that individuals with severe OSA who lived in lower income neighborhoods did not face obstacles in obtaining PAP treatment; however, they did observe that those living in higher income neighborhoods had a 27% higher rate of PAP acceptance.…”
Section: Discussionmentioning
confidence: 99%